Princess Pru and the ogre on the hill - Fergus, Maureen (Oggy and Pru, 2023)
"Princess Pru's life was practically perfect. She had two loving dads, an ostrich named Orville, and three royal tarantulas. And then one day, a ghastly ogre with crusty toenails and goopy ears moves into the house on the hill. At first, Pru sees the ogre as a nuisance: he disrupts her royal rock band practices, weekly tickle tag games, and even the hide-and-seek tournament. The townspeople are also suspicious--everyone knows ogres hate seeing people have fun. But Pru starts to wonder if the ogre is just lonely and asks her dads, the kings, if she can throw him a "Welcome to the Kingdom" party, which her over-protective parents refuse. As alarming reports about the ogre's behavior roll in--he's spotted buying cupcakes, craft supplies, and balloons--the people of the kingdom are terrified. When they receive ominous notes, which readers, like Pru, will recognize as invitations, the kings imagine the ogre plans to put them all in a stew. But Pru heads for the house on the hill at the appointed time, where she's greeted by the ogre for a party. He simply wanted to make friends. With her courage, Pru clears the way for the others to join the fun, and they spend the afternoon playing games and eating ogre-licious cupcakes with Oggy the ogre, who becomes Pru's fast friend. This heartwarming, humorous story about genuine friendship shows Pru accepting Oggy as he is, ear goop and all, and nudges the reader to do the same and not judge based on appearances."--